Mechanical Properties, Formability, and Corrosion Behavior of Dual Phase Weathering Steels Developed by an Inter‐Critical Annealing Treatment. Issue 3 (3rd May 2014) - Allam, Tarek; Abbas, Mahmoud
<x xml:space="preserve">Abstract</x> Dual phase weathering (DP‐weathering) steels were developed by inter‐critical annealing treatments from a commercial hot‐rolled weathering steel. The effects of martensite volume fraction (MVF) and microstructural changes accompanied the martensitic transformation on mechanical properties, formability, and corrosion behavior were investigated by metallography, mechanical, and corrosion testing. The investigations revealed that the final microstructures consisted mostly of island‐shape martensite particles impeded in a ferrite matrix except for the highest temperature of 840 °C. Depending on MVF and martensite morphology, a wide range of mechanical properties was achieved; yield strength of 370–408 MPa and tensile strength of 580–689 MPa. The coupling of the results from metallography and mechanical testing emphasized the enhanced formability of the developed DP‐weathering steels. The optimum combination of strength and formability was achieved for specimens treated at 810 °C and attained a MVF of 26%. Although, the presence of martensite phase raised the corrosion rate of DP‐weathering steels during the initial corrosion cycles, it accelerated the nucleation process of the protective FeOOH layer. X‐ray diffraction (XRD) investigations demonstrated that the rust layers formed on DP‐weathering steels composed mainly of γ‐FeOOH, α‐FeOOH, and FexO.